Endoscopic biopsy of cystic intracerebral tumours. (June 2013) - Akmal, S.; Flint, G.
Abstract This technical note describes the application of neuroendoscopy for decompressing and obtaining tissue samples from cystic intracerebral tumours. The method provides for visualisation of the solid tumour component prior to biopsy and retains the advantages of being a burr hole procedure.